The viability of Islamic finance as a socio-economic solution for urban Muslim minorities in America - Gonsalves, Richard Gerald (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
The first Muslims in America were the slaves brought over to work the American sugar and cotton plantations. These Muslims faced extraordinary hardships and were forced to convert to Christianity. Generations later, large numbers of African Americans are now returning to the religion of their ancestors, and as African American Muslims they face new unique challenges. The objective of this research is to identify the economic and social challenges faced by African American Muslims and to assess the viability of using Islamic finance as a solution to some of these problems. To achieve this objective the literature on how financial institutions can affect economic growth and development was analysed and the different types of socially driven financial institutions and their effectiveness at poverty alleviation was discussed. Additionally a survey was also conducted to assess the viability of an Islamic financial institution for African American Muslims. The research focussed its viability study in Philadelphia and its surrounding areas, as this is an area with a large concentration of African American Muslims. A survey was used to gather the views of the African American Muslim residents of this area and was analysed in conjunction with the available literature to build a framework for an Islamic financial institution that could address the issues and challenges faced by African American Muslims in this area using the principles of Islamic finance.